Women's leadership gamut in Saudi Arabia's higher education sector - Hammad Akbar (23275510) (2023)
This paper explores women's leadership in Saudi Arabia's three university settings—gender segregated (women or men‐only), unsegregated (co‐educational) and the majority of partially segregated universities where women's campuses exist within male‐dominated universities. While Saudi Arabia's accelerated reforms are creating new opportunities for women's leadership, these are not reflected in the higher education sector yet. In adopting a feminist institutional theory perspective, this study employed a feminist qualitative approach, including 14 semi‐structured interviews in Saudi Arabia's three university settings. The findings revealed that the barriers to women's leadership were most significant within the partially segregated universities, rendering women leaders as effectively powerless. In contrast, women's leadership flourished in the women‐only university setting. As such, the findings suggest that the dominating partially segregated model is ineffective and problematic for women's leadership, and contradict the dominant view that gender segregation disempowers women. These insights have implications for the transformation of Saudi Arabia's higher education sector, aligned with the Kingdom's Vision 2030 policy. Other Information Published in: Gender, Work & Organization License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/gwao.13003